Police studies program for youth at risk: The role of police distributive justice and personal morality in explaining police legitimacy - Azmy, Ameen (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
This study examined a unique police studies intervention program by comparing two groups of youth-at-risk in two types of residential youth schools. The experimental group included 129 youths who had attended a police studies program, while the control group included 167 youths who had attended a different intervention program, without police studies. We hypothesized that the experimental group would have more positive perceptions of police legitimacy and distributive justice and higher levels of personal morality than the control group would. Moreover, we hypothesized that the relationship between the type of the intervention program and perceptions of police legitimacy would be explained by youths’ personal morality and perceptions of police distributive justice. The study showed that the experimental group had more positive perceptions of police legitimacy and higher personal morality than did the control group, but there were no differences in perceived police distributive justice between the two groups. In addition, while personal morality partly mediated the link between the type of intervention program and perceptions of police legitimacy, perceived police distributive justice did not. Empirical and theoretical implications are discussed.